Caring for cognitively impaired older patients in the general hospital: A qualitative analysis of similarities and differences between a specialist Medical and Mental Health Unit and standard care wards - Goldberg, Sarah E.; Whittamore, Katherine H.; Pollock, Kristian; Harwood, Rowan H.; Gladman, John R.F. (Elsevier, 2014)
Background: Around half of people aged over 70 admitted as an emergency to general hospital have dementia, delirium or both. Dissatisfaction is often expressed about the quality of hospital care. A medical and mental health unit was developed to provide best practice care to cognitively impaired older patients. The Unit was evaluated by randomised controlled trial compared to standard care wards. Part of this evaluation involved structured non-participant observations of a random sub-sample of participants and the recording of field notes. Objectives: The aim of this paper is to compare and contrast the behaviours of staff and patients on the Medical and Mental Health Unit and standard care wards and to provide a narrative account that helps to explain the link between structure, process and reported outcomes. Design: Field notes were analysed using the constant comparison method. Setting: A large hospital within the East Midlands region of the United Kingdom. Participants: Patient participants were aged over 65, and identified by Admissions Unit physicians as being ‘confused’. Most patients had delirium or dementia. Results: Sixty observations (360 hours) were made between March and December 2011. Cognitively impaired older patients had high physical and psychological needs, and were cared for in environments which were crowded, noisy and lacked privacy. Staff mostly prioritised physical over psychological needs. Person-centred care on the Medical and Mental Health Unit was mostly delivered during activity sessions or meal times by activities coordinators. Patients on this unit were able to walk around more freely than on other wards. Mental health needs were addressed more often on the Medical and Mental Health Unit than on standard care wards but most staff time was still taken up delivering physical care. More patients called out repetitively on the Unit and staff were not always able to meet the high needs of these patients. Conclusion: Care provided on the Medical and Mental Health Unit was distinctly different from standard care wards. Improvements were worthwhile, but care remained challenging and consistent good practice was difficult to maintain. Disruptive vocalisation may have been provoked by concentrating cognitively impaired patients on one ward.